Intriguing and Beautiful: Adamacrocera adami gen. et sp. nov. from the Upper Cretaceous Amber of Myanmar Represents a New Subfamily of Keroplatidae (Diptera: Bibionomorpha) - Ševčík, Jan; Krzemiński, Wiesław; Skibińska, Kornelia (Insects, 2020)
A new fossil genus and species of Keroplatidae (Diptera, Bibionomorpha, Sciaroidea), Adamacrocera adami gen. et sp. nov., from the Upper Cretaceous Burmese amber is described and illustrated. Based on morphological evidence, it is placed in a new subfamily Adamacrocerinae subfam. nov. The new genus, as well as the subfamily, possesses the wing venation characteristic of the genera of some Sciaroidea incertae sedis, as well as that of the fossil families Archizelmiridae, Antefungivoridae and Mesosciophilidae, in combination with macrocerine-like habitus and male terminalia.
Keywords: inclusions; taxonomy; new genus; fossil insects; Mesozoic; Sciaroidea